The Potential Impact and Usability of the Eighth Edition TNM Staging Classification in Oral Cavity Cancer. Issue 10 (October 2021) - Chiu, K.; Hosni, A.; Huang, S.H.; Tong, L.; Xu, W.; Lu, L.; Bayley, A.; Bratman, S.; Cho, J.; Giuliani, M.; Kim, J.; Ringash, J.; et al.
Abstract: Aims: In the current eighth edition head and neck TNM staging, extranodal extension (ENE) is an adverse feature in oral cavity squamous cell cancer (OSCC). The previous seventh edition N1 with ENE is now staged as N2a. Seventh edition N2+ with ENE is staged as N3b in the eighth edition. We evaluated its potential impact on patients treated with surgery and postoperative intensity-modulated radiotherapy (IMRT). Materials and methods: OSCC patients treated with primary surgery and adjuvant (chemo)radiotherapy between January 2005 and December 2014 were reviewed. Cohorts with pathological node-negative (pN–), pathological node-positive without ENE (pN+_pENE–) and pathological node-positive with ENE (pN+_pENE+) diseases were compared for local control, regional control, distant control and overall survival. The pN+ cohorts were further stratified into seventh edition N-staging subgroups for outcomes comparison. Results: In total, 478 patients were evaluated: 173 pN–; 159 pN+_pENE–; 146 pN+_pENE+. Outcomes at 5 years were: local control was identical (78%) in all cohorts ( P = 0.892), whereas regional control was 91%, 80% and 68%, respectively ( P < 0.001). Distant control was 97%, 87%, 68% ( P < 0.001) and overall survival was 75%, 53% and 39% ( P < 0.001), respectively. Overall survival for N1 and N2a subgroups was not significantly different. In the seventh edition N2b subgroup of pENE– ( n = 79) and pENE+ ( n = 79) cohorts, overall survival was 67% and 37%, respectively. In the seventh edition N2c subgroups, overall survival for pENE– ( n = 17) and pENE+ ( n = 38) cohorts was 65% and 35% ( P = 0.08), respectively. Overall, an additional 128 patients (42% pN+) were upstaged as N3b. Conclusions: When eighth edition staging was applied, stage migration across the N2–3 categories resulted in expected larger separations of overall survival by stage. Patients treated with primary radiation without surgical staging should have outcomes carefully monitored. Strategies to predict ENE preoperatively and trials to improve the outcomes of pENE+ patients should be explored. Highlights: Wide separation of survival across N2–3 categories of oral cavity cancer patients. Challenges with clinical staging without surgical/pathological evaluation of extranodal extension in oral cavity cancer. Unsatisfactory survival in oral cavity cancer patients with extranodal extension despite multimodality treatment. Consideration of alternative therapeutic approach for advanced oral cavity cancer.